Targeting metabolic reprogramming to overcome immune tolerance in melanoma immunotherapy - Wang, Qinchen; Shi, Lei; Shi, Daoming; Tai, Ningzheng; Wang, Xu (Frontiers in Immunology, 2025)
Significant advances in the treatment of melanoma, the most aggressive form of skin cancer, have been achieved via immunotherapy. Despite these improvements, therapeutic resistance remains a formidable challenge, compromising the treatment efficacy and patient outcomes. This review delves into the intricate mechanisms driving immunotherapy resistance in melanoma, emphasizing alterations in key metabolic pathways, changes within the tumor microenvironment, and the critical role of the gut microbiota. This review also examines how metabolic reprogramming supports tumor proliferation and immune evasion, it highlights the impact of extracellular acidification and angiogenic processes on resistance development. By synthesizing current insights, this review emphasizes the importance of targeting these multifaceted interactions to overcome resistance, thereby paving the way for more effective and durable therapeutic strategies in melanoma treatment.